Evaluasi Perencanaan Obat Generik Dengan Metode ABC Di Apotek Anugrah Abadi Surakarta - Putri, Puji Wahyu Arista; Wahyuningsih, Sri Saptuti; Endrawati, Susi; Rejeki, Sri (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2024)
Anugrah Abadi Pharmacy is a pharmacy that has many patients and a complete range of medicines. Pharmacies still often experience shortages of medicines, which discrupts service to patients. This needs to be evaluated interms of drug planning, one of which is through the ABC method. The study was conducted to determine the grouping of generic drugs based on ABC analysis and determine the total budget of generic drug funds for procuring supplies at Anugrah Abadi Surakarta Pharmacy during the July-December 2022 period. This study is a non-experimental study with descriptive analysis usingf quantity data retrospectively by taking data on generic drug consumption sold in the July-December 2022 period. Data is processed using Microsoft Excel 2007 and grouping A, B, C and calculated the total planning budget. The results of the study obtained 112 kinds of generic drug items, group A as many as 27 items with a total use of 206,798 tabs / flas / tube and a budget of Rp. 141,959,700 (70%), group B as many as 32 items with a total use of 54,400 tabs / flas / tube and a budget of Rp. 40,654,300 (20%), group C as many as 53 items with a total use of 25,794 tabs / flas / tube and a budget of Rp. 18,195,400 (10%). Conclusion group A drugs use the most budget, therefore they must be controlled regularly.